2011
DOI: 10.1074/jbc.m110.195537
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput Screening Uncovers a Compound That Activates Latent HIV-1 and Acts Cooperatively with a Histone Deacetylase (HDAC) Inhibitor

Abstract: Current antiretroviral therapy (ART) provides potent suppression of HIV-1 replication. However, ART does not target latent viral reservoirs, so persistent infection remains a challenge. Small molecules with pharmacological properties that allow them to reach and activate viral reservoirs could potentially be utilized to eliminate the latent arm of the infection when used in combination with ART. Here we describe a cellbased system modeling HIV-1 latency that was utilized in a high-throughput screen to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…A recently reported high-throughput screening using SupT1 cells latently infected with a GFP and secretable alkaline phosphatase encoding HIV identified a new activator (AV6) of HIV-1 which required NFAT and synergized with the HDAC inhibitor valproic acid (55). Our data have shown that MMQO activity on HIV is independent of NFAT activation, as it was not affected by cyclosporine or FK506 (data not shown).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…A recently reported high-throughput screening using SupT1 cells latently infected with a GFP and secretable alkaline phosphatase encoding HIV identified a new activator (AV6) of HIV-1 which required NFAT and synergized with the HDAC inhibitor valproic acid (55). Our data have shown that MMQO activity on HIV is independent of NFAT activation, as it was not affected by cyclosporine or FK506 (data not shown).…”
Section: Discussionmentioning
confidence: 47%
“…S2 in the supplemental material). Its structure was a new variation, different from the class 1 quinolin-8-ol and the MMQO quinolin-4-ol, and it partially resembles the AV6 compound recently reported elsewhere (55). Due to the structural coincidence between MMQA and the quinolinamine moiety of AV6, we cannot rule out the possibility that MMQA acts on a different pathway than that of MMQO.…”
Section: Discussionmentioning
confidence: 84%
“…The observations presented here also have implications for screening efforts geared toward the discovery of antilatency drugs (52)(53)(54). In particular, screening methods that use cells in division may favor the discovery of substances that elicit dissociation of P-TEFb from the 7SK RNP complex, for example, HMBA.…”
Section: Fig 6 In Resting Cd4mentioning
confidence: 98%
“…RNA stability was reported to be important for activation of latent HIV (Micheva-Viteva et al, 2011), however cis-acting RNA stability-regulating sequences were identified in gag-pol , but not in tat mRNA (Schwartz et al, 1992). More recently, viral RNA stability as a key mediator of latency and reactivation was also described for the Kaposi’s associated herpesvirus (KSHV).…”
Section: Discussionmentioning
confidence: 99%